Cross-Cultural Differences in Consistent Mapping Effects of Targets and Distractors. (May 2016) - Lee, Donghoon; Shin, Hyun Jung; Weldon, Rebecca B.; Sohn, Myeong-Ho
Previous cross-cultural studies have shown that East Asians pay more attention to the background information and European Americans more to the focal object. However, it has not been well investigated what cognitive benefits can be achieved with these different attention allocation strategies. In the current study, we examined whether Koreans and European Americans differ in utilizing the regularity in targets and distractors by comparing consistent mappings (CMs) with varied mappings (VMs) of stimuli. Two experiments consistently revealed that European Americans showed a greater performance benefit with the consistency embedded within the targets (i.e., the CM target effect) but not within the distractors. In contrast, Koreans showed a greater performance benefit with the consistency within the distractors (i.e., the CM distractor effect), but not within the targets. These results imply that the East–West differences in attention allocation strategies reflect the cultural differences in utilizing the information that is potentially beneficial for task performance. We discuss what kinds of cognitive benefits can be achieved by differentially paying attention to the target and the background.